PENGARUH ALELOPATI SERESAH DAUN BAMBU (Dendrocalamus asper) PADA PERKECAMBAHAN KEDELAI (Glycine max L. Merril) - Lutfy Ditya Cahyanti (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
Weeds are an important factor in the decline of soybean  production. One of weed control techniques that can be done is to use alelopati as an bioherbicide. One source of allelopathy that can be utilized as bioherbicide is bamboo leaf litter. Problems arise if this alelopati also affect the pattern of germination cultivation plants because one of the main requirements of bioherbisida is not to affect the growth and development of crops. The purpose of this study was to determine whether leaf litter alelopathy would affect the germination of soybeans. The hypothesis this research is that bamboo leaf litter alelopathy will not affect the germination of soybean crops so it will be safe to use as a pre-plant bioherbicide. The treated treatment is without litter solution of bamboo leaf, and dosage of 5%, 10%, and 15% bamboo leaf litter solution. The design used was a complete non factorial randomized design with 5x replication. The conclusion of this research is the treatment of allelopathy given by application of bamboo leaf litter with various doses has no significant effect on the germination, sprout length, and germination time of soybean crop, so that bamboo leaf litter solution is safe to be used as bioherbicide on sustainable agriculture.